Method for preparing boron-doped carbon-based iron monatomic material through two-step calcination and application of boron-doped carbon-based iron monatomic material
By doping boron elements into carbon-based materials and using soft templates and two-step calcination methods, boron-doped carbon-based iron single atomic materials were prepared, which solved the problems of insufficient stability and limited catalytic activity of iron single atomic catalysts, and achieved efficient catalytic performance and stability, which was suitable for water pollution repair.
Patent Information
- Application Number
- CN202411552992.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The insufficient stability of iron single atom catalyst on the support and the limited catalytic activity limit their application in environmental catalytic reactions.
By doping boron elements into the carbon-based material, combining soft templates and two-step calcination method, boron-doped carbon-based iron single atomic material is prepared, which improves the conductivity and activity of the material and enhances the catalytic performance and stability.
The uniform distribution and efficient catalysis of iron single atoms are achieved, and the stability and catalytic efficiency of the material are improved, especially in pollution repair applications in water bodies, which show excellent removal performance.
Smart Images

Figure CN119500218A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional nanomaterials and technologies, and specifically relates to a carbon-based iron single-atom material derived from boron-doped chitin, and a preparation method and application thereof. Background Art
[0002] With the rapid development of single-atom catalyst research, single-atom materials have gradually become a research hotspot in the field of environmental pollution control due to their high atomic utilization, uniform distribution of active sites and excellent catalytic performance. Especially in the fields of wastewater treatment, degradation of organic pollutants and energy conversion, single-atom catalysts have shown great potential. However, although iron single-atom catalysts have been widely used in environmental catalytic reactions due to their abundant crustal resources, low cost and good catalytic activity, there are still some limitations in their actual application, such as the insufficient stability of iron single atoms on the carrier and limited catalytic activity.
[0003] In recent years, carbon-based materials have become good single-atom carrier materials due to their excellent conductivity, structural adjustability and large specific surface area. By doping other elements in carbon-based materials, their electronic structure can be further regulated, thereby improving the catalytic performance and stability of single atoms. For example, boron, as a trivalent element, can cause electron rearrangement around carbon atoms when doped in carbon-based materials, breaking the sp 2 structure, so that its electrons are carp and the catalytic activity is enhanced. In addition, boron doping can also effectively improve the electrochemical properties of the material, enhance the stability of the iron single atom on the carbon carrier, and thus improve its catalytic efficiency. Based on this, the present invention uses ferric chloride hexahydrate as the iron source and chitin as the nitrogen and carbon source, and synthesizes a boron-doped carbon-based iron single atom material by soft template and two-step calcination method. First, the doping of boron atoms can effectively break the local structure of the carbon material, making the distribution of the iron single atom on the carbon-based material more uniform, while improving the conductivity and activity of the material. Secondly, boron doping can also improve the electronic structure of the iron single atom and further enhance the efficiency of the catalytic reaction. In addition, chitin itself contains nitrogen and the natural and special three-dimensional network structure provides a good environment for the coordination of metals. In short, this invention provides a new design idea and technical method reference for the same type of non-metal-doped carbon-based single-atom nanomaterials. Summary of the invention
[0004] The purpose of the present invention is to address the deficiencies in the prior art and provide a method for preparing and applying a boron-doped carbon-based iron single-atom material.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a boron-doped carbon-based iron single-atom material by two-step calcination, comprising the following steps:
[0007] Step 1: Place the carbon-based reagent, iron reagent and soft template into anhydrous ethanol respectively;
[0008] Step 2: ultrasonically treating the carbon-based reagent solution, the iron reagent solution and the soft template solution obtained in step 1, and then placing them in an oil bath and heating them to 55-70° C.;
[0009] Step 3: Add the heated iron reagent solution and the soft template solution to the heated carbon-based reagent solution, wait for the ethanol to evaporate, and place in an oven to dry;
[0010] Step 4: The material obtained in step 3 is simply ground and placed in a quartz boat. Argon gas is passed through the internal pipeline of the tube furnace for 10-30 minutes to exhaust all the air in the pipeline. The temperature is increased to 800-850°C at a rate of 9-10°C / min and maintained for 2-2.5 hours, then cooled to room temperature and taken out;
[0011] Step 5: Grind the solid obtained in step 4, wash it with water and ethanol 3 to 4 times each, and then dry it in a vacuum drying oven for 16 to 36 hours;
[0012] Step 6: Grind the dried material prepared in step 5 into powder; take 350-450 mg of the powder, then add 40-120 mg of boric acid and grind and mix thoroughly;
[0013] Step 7: Place the mixture obtained in step 6 into a quartz boat, pass argon gas through the internal pipeline of the tube furnace for 10 to 30 minutes to exhaust all the air in the pipeline; increase the temperature to 400 to 450° C. at a heating rate of 9 to 10° C. / min, maintain for 2 to 2.5 hours, and then cool to room temperature before taking out;
[0014] Step 8: Grind the solid obtained in step 7, wash it with water and ethanol 3 to 4 times each, and then dry it in a vacuum drying oven for 16 to 36 hours;
[0015] Step nine: Grind the dry material prepared in step eight into powder to obtain a boron-doped carbon-based iron single atom material.
[0016] In the above method, the iron reagent includes ferric chloride hexahydrate; the carbon-based reagent includes chitin; the soft template includes polyether F127; and the method used is a soft template + two-step calcination strategy. In the present invention, polyether F127 is used as a soft template, ferric chloride hexahydrate is used as an iron source, and chitin is used as a nitrogen and carbon source.
[0017] In the above method, in step 2, the ultrasonic time is 20-30 minutes.
[0018] In the above method, in step 3, the drying temperature in the oven is 50-70°C.
[0019] Furthermore, the iron reagent includes ferric chloride hexahydrate, the carbon-based reagent includes chitin, the soft template includes polyether F127, and the method used is a soft template + two-step calcination strategy.
[0020] In a second aspect, the present invention provides a boron-doped carbon-based iron single atom material prepared by the above method.
[0021] In a third aspect, the present invention provides an application of a boron-doped carbon-based iron single-atom material, wherein the boron-doped carbon-based iron single-atom material is used for the efficient degradation of sulfamethoxazole.
[0022] Furthermore, the application comprises the following steps:
[0023] (1) dissolving sulfamethoxazole in a beaker, and then adjusting the volume in a volumetric flask to obtain a sulfamethoxazole contaminated solution;
[0024] (2) placing the boron-doped carbon-based iron single-atom material into the conical flask containing the sulfamethoxazole contaminant in step (1), and performing magnetic stirring;
[0025] (3) Add PMS reagent to the conical flask containing the material and pollutants in step (2).
[0026] Furthermore, the concentration of sulfamethoxazole in the sulfamethoxazole contaminated solution in step (1) is 3-5 mg / L, preferably 5 mg / L.
[0027] Furthermore, in step (2), the dosage of the boron-doped carbon-based iron single-atom material is 0.3 to 0.45 g / L.
[0028] Furthermore, the dosage of the PMS reagent in step (3) is 0.6-1.2 mM.
[0029] The material prepared by the present invention retains the high crystalline fiber sheet structure of chitin. When applied to the persulfate-based advanced oxidation technology, the antibiotic sulfamethoxazole in the water can be completely removed within 50 minutes. The synthesis method proposed by the present invention realizes the introduction of boron atoms into the carbon-based iron single-atom material. The catalyst performance of the prepared material is excellent, which can provide new ideas for the structural design of carbon-based iron single-atom nanomaterials for application in water pollution remediation.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The introduction of the soft template in the present invention promotes the dispersion of single iron atoms;
[0032] (2) The doping of boron atoms in the present invention improves the electronic structure of the iron single atom, increases the conductivity and activity of the material, and enhances its catalytic activity;
[0033] (3) The method of the present invention utilizes chitin with a special three-dimensional network structure as a nitrogen and carbon source, which not only realizes nitrogen self-doping, but also provides an excellent environment for iron coordination due to its rich biological functional groups;
[0034] (4) The method of the present invention will not cause iron pollution due to the use of iron salts.
[0035] (5) The material of the present invention introduces boron atoms into the carbon-based iron single atom material through two-step calcination, which not only improves the excellent catalytic performance of the iron single atom, but also improves the stability of the material.
[0036] (6) The material of the present invention has excellent removal performance for sulfamethoxazole in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1a and 1b These are scanning electron microscope images of carbon-based iron single atom material and boron-doped carbon-based iron single atom material;
[0038] Figure 2a and 2b These are transmission electron microscope images of carbon-based iron single atom material and boron-doped carbon-based iron single atom material.
[0039] Figure 3 This is a high-angle annular dark-field scanning transmission electron microscopy image of boron-doped carbon-based iron single atom material.
[0040] Figure 4 X-ray diffraction patterns of carbon-based iron single-atom materials and boron-doped carbon-based iron single-atom materials;
[0041] Figure 5a This is the N1s high-resolution XPS spectra of carbon-based iron single-atom materials and boron-doped carbon-based iron single-atom materials. Figure 5b This is the B1s high-resolution XPS spectrum of boron-doped carbon-based iron single-atom material;
[0042] Figure 6 (a), (b) and (c) are the electrochemical impedance spectroscopy, Taaffe plot and open circuit voltage test diagram of carbon-based iron single atom material and boron-doped carbon-based iron single atom material, respectively.
[0043] Figure 7 This is a graph showing the change of sulfamethoxazole concentration in the reaction system over time. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0045] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0046] Example 1 A carbon-based iron single-atom material (Fe-N x / GCN)
[0047] Step 1: Place 7 g chitosan, 50 mg ferric chloride hexahydrate and 0.7 g polyether F127 in anhydrous ethanol respectively;
[0048] Step 2: ultrasonically treat the chitosan solution obtained in step 1, the ferric chloride hexahydrate solution obtained in step 1, and the polyether F127 solution obtained in step 1 for 20 minutes, and then respectively place them in an oil bath and heat them to 60° C.;
[0049] Step 3: Add the ferric chloride hexahydrate solution and the polyether F127 solution obtained in step 2 to the chitosan solution obtained in step 2, wait for the ethanol to evaporate, and dry in an oven at 60° C.;
[0050] Step 4: Grind the material obtained in step 3 briefly and put it into a quartz boat. Pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 800℃ at a rate of 10℃ / min and maintain for 2h, then cool to room temperature and take out;
[0051] Step 5: simply grind the solid obtained in step 4, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0052] Step 6: Grind the dried material prepared in step 5 into powder and put it into a quartz boat. Pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 400℃ at a rate of 10℃ / min and maintain for 2h, then cool to room temperature and take out;
[0053] Step 7: simply grind the solid obtained in step 6, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0054] Step 8: Grind the dried material prepared in step 7 into powder to obtain a carbon-based iron single-atom material (Fe-N x / GCN).
[0055] Example 2 A boron-doped carbon-based iron single-atom material (Fe-N x Preparation of B / GCN4
[0056] Step 1: Place 7 g chitosan, 50 mg ferric chloride hexahydrate and 0.7 g polyether F127 in anhydrous ethanol respectively;
[0057] Step 2: ultrasonically treat the chitosan solution obtained in step 1, the ferric chloride hexahydrate solution obtained in step 1, and the polyether F127 solution obtained in step 1 for 20 minutes, and then respectively place them in an oil bath and heat them to 60° C.;
[0058] Step 3: Add the ferric chloride hexahydrate solution and the polyether F127 solution obtained in step 2 to the chitosan solution obtained in step 2, wait for the ethanol to evaporate, and dry in an oven at 60° C.;
[0059] Step 4: Grind the material obtained in step 3 briefly and put it into a quartz boat. Pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 800℃ at a rate of 10℃ / min and maintain for 2h, then cool to room temperature and take out;
[0060] Step 5: simply grind the solid obtained in step 4, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0061] Step 6: Grind the dry material prepared in step 5 into powder, weigh 400 mg of the powder, and then add 40 mg of boric acid to grind and mix thoroughly.
[0062] Step 7: Place the mixture obtained in step 6 into a quartz boat, and pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 400°C at a rate of 10°C / min, and maintain for 2 hours, then cool to room temperature and take out;
[0063] Step 8: simply grind the solid obtained in step 7, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0064] Step 9: Grind the dried material prepared in step 8 into powder to obtain a boron-doped carbon-based iron single-atom material (Fe-N x B / GCN4).
[0065] The amount of boric acid used in Example 2 is 40 mg, so the boron-doped carbon-based iron single-atom material prepared in this example is marked as Fe-N x B / GCN4.
[0066] Example 3 A boron-doped carbon-based iron single-atom material (Fe-N xPreparation of B / GCN6
[0067] Step 1: Place 7 g chitosan, 50 mg ferric chloride hexahydrate and 0.7 g polyether F127 in anhydrous ethanol respectively;
[0068] Step 2: ultrasonically treat the chitosan solution obtained in step 1, the ferric chloride hexahydrate solution obtained in step 1, and the polyether F127 solution obtained in step 1 for 20 minutes, and then respectively place them in an oil bath and heat them to 60° C.;
[0069] Step 3: Add the ferric chloride hexahydrate solution and the polyether F127 solution obtained in step 2 to the chitosan solution obtained in step 2, wait for the ethanol to evaporate, and dry in an oven at 60° C.;
[0070] Step 4: Grind the material obtained in step 3 briefly and put it into a quartz boat. Pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 800℃ at a rate of 10℃ / min and maintain for 2h, then cool to room temperature and take out;
[0071] Step 5: simply grind the solid obtained in step 4, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0072] Step 6: Grind the dry material prepared in step 5 into powder, weigh 400 mg of the powder, and then add 60 mg of boric acid to grind and mix thoroughly.
[0073] Step 7: Place the mixture obtained in step 6 into a quartz boat, and pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 400°C at a rate of 10°C / min, and maintain for 2 hours, then cool to room temperature and take out;
[0074] Step 8: simply grind the solid obtained in step 7, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0075] Step 9: Grind the dried material prepared in step 8 into powder to obtain a boron-doped carbon-based iron single-atom material (Fe-N x B / GCN6).
[0076] The amount of boric acid used in Example 3 is 60 mg, so the boron-doped carbon-based iron single-atom material prepared in this example is marked as Fe-N x B / GCN6.
[0077] Example 4 A boron-doped carbon-based iron single-atom material (Fe-N x Preparation of B / GCN8
[0078] Step 1: Place 7 g chitosan, 50 mg ferric chloride hexahydrate and 0.7 g polyether F127 in anhydrous ethanol respectively;
[0079] Step 2: ultrasonically treat the chitosan solution obtained in step 1, the ferric chloride hexahydrate solution obtained in step 1, and the polyether F127 solution obtained in step 1 for 20 minutes, and then respectively place them in an oil bath and heat them to 60° C.;
[0080] Step 3: Add the ferric chloride hexahydrate solution and the polyether F127 solution obtained in step 2 to the chitosan solution obtained in step 2, wait for the ethanol to evaporate, and dry in an oven at 60° C.;
[0081] Step 4: Grind the material obtained in step 3 briefly and put it into a quartz boat. Pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 800℃ at a rate of 10℃ / min and maintain for 2h, then cool to room temperature and take out;
[0082] Step 5: simply grind the solid obtained in step 4, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0083] Step 6: Grind the dry material prepared in step 5 into powder, weigh 400 mg of the powder, and then add 80 mg of boric acid to grind and mix thoroughly.
[0084] Step 7: Place the mixture obtained in step 6 into a quartz boat, and pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 400°C at a rate of 10°C / min, and maintain for 2 hours, then cool to room temperature and take out;
[0085] Step 8: simply grind the solid obtained in step 7, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0086] Step 9: Grind the dried material prepared in step 8 into powder to obtain a boron-doped carbon-based iron single-atom material (Fe-N x B / GCN8).
[0087] The amount of boric acid used in Example 4 is 80 mg, so the boron-doped carbon-based iron single-atom material prepared in this example is marked as Fe-N x B / GCN8.
[0088] Example 5 A boron-doped carbon-based iron single-atom material (Fe-N x Preparation of B / GCN12
[0089] Step 1: Place 7 g chitosan, 50 mg ferric chloride hexahydrate and 0.7 g polyether F127 in anhydrous ethanol respectively;
[0090] Step 2: ultrasonically treat the chitosan solution obtained in step 1, the ferric chloride hexahydrate solution obtained in step 1, and the polyether F127 solution obtained in step 1 for 20 minutes, and then respectively place them in an oil bath and heat them to 60° C.;
[0091] Step 3: Add the ferric chloride hexahydrate solution and the polyether F127 solution obtained in step 2 to the chitosan solution obtained in step 2, wait for the ethanol to evaporate, and dry in an oven at 60° C.;
[0092] Step 4: Grind the material obtained in step 3 briefly and put it into a quartz boat. Pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 800℃ at a rate of 10℃ / min and maintain for 2h, then cool to room temperature and take out;
[0093] Step 5: simply grind the solid obtained in step 4, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0094] Step 6: Grind the dry material prepared in step 5 into powder, weigh 400 mg of the powder, and then add 120 mg of boric acid to grind and mix thoroughly.
[0095] Step 7: Place the mixture obtained in step 6 into a quartz boat, and pass argon gas through the internal pipeline of the tube furnace for 20 minutes to exhaust all the air in the pipeline. Raise the temperature to 400°C at a rate of 10°C / min, and maintain for 2 hours, then cool to room temperature and take out;
[0096] Step 8: simply grind the solid obtained in step 7, wash it with water and ethanol three times each, and then dry it in a vacuum drying oven for 24 hours;
[0097] Step 9: Grind the dried material prepared in step 8 into powder to obtain a boron-doped carbon-based iron single-atom material (Fe-N x B / GCN8).
[0098] The amount of boric acid used in Example 5 is 120 mg, so the boron-doped carbon-based iron single-atom material prepared in this example is marked as Fe-N x B / GCN12.
[0099] Application Example 1 Scanning Electron Microscope Test
[0100] The carbon-based iron single-atom material (Fe-N x / GCN) and the boron-doped carbon-based iron single-atom material (Fe-N x B / GCN12) were tested by scanning electron microscope, and the test results were as follows Figure 1a and Figure 1b shown.
[0101] from Figure 1a and Figure 1b It can be seen that the materials (Fe-N x / GCN and Fe-N x B / GCN12) retains the high crystalline fiber lamellar structure of chitosan, and presents a layered stacking structure after two-step calcination. The introduction of boric acid in Example 5 does not destroy this structure.
[0102] Application Example 2 Transmission Electron Microscope Test
[0103] The carbon-based iron single-atom material (Fe-N x / GCN) and the boron-doped carbon-based iron single-atom material (Fe-N x B / GCN12) were tested by transmission electron microscopy, and the test results were as follows Figure 2a and Figure 2b shown.
[0104] from Figure 2a , Figure 2b It can be seen that the materials (Fe-N x / GCN and Fe-N x B / GCN12) is a two-dimensional layered nanosheet structure.
[0105] Application Example 3 High-angle annular dark field scanning transmission electron microscope test
[0106] The boron-doped carbon-based iron single-atom material (Fe-N x B / GCN12) was tested by high-angle annular dark field scanning transmission electron microscope. The test results are as follows Figure 3 shown.
[0107] from Figure 3 It can be seen that the material (Fe-N x B / GCN12), there are many single bright spots, which indicates that Fe exists in the form of single isolated atoms.
[0108] Application Example 4: X-ray diffraction test experiment
[0109] The carbon-based iron single-atom material (Fe-N x / GCN) and the boron-doped carbon-based iron single-atom material (Fe-N x B / GCN12) was tested by X-ray diffraction, and the test results are as follows Figure 4 shown.
[0110] from Figure 4 It can be seen that the materials (Fe-N x / GCN and Fe-N x B / GCN12) both belong to the typical hexagonal graphite carbon structure.
[0111] Application Example 5: X-ray Photoelectron Spectroscopy Test
[0112] The carbon-based iron single-atom material (Fe-N x / GCN) and the boron-doped carbon-based iron single-atom material (Fe-N x B / GCN12) was subjected to X-ray photoelectron spectroscopy test, and the test results are shown in FIG5 .
[0113] Figure 5a Carbon-based iron single-atom materials (Fe-N x / GCN and boron-doped carbon-based iron single-atom materials (Fe-N x The binding energies of pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and oxidized nitrogen appeared in B / GCN12, indicating that nitrogen was successfully doped in the form of self-doping. In addition, the peaks of nitrogen coordinated iron formed by hybridization of Fe orbitals and N axial ligands also appeared in the N1s spectra of both, which also indicated that iron was distributed in a single atomic manner. Figure 5b Boron-doped carbon-based iron single atom material (Fe-N x The presence of CBN bonds was detected in the B1s spectrum of B / GCN12), which also indicates that boron atoms were successfully doped into the carbon-based iron single atom material.
[0114] Application Example 6 Electrochemical Experiment
[0115] The carbon-based iron single-atom material (Fe-N x / GCN) and the boron-doped carbon-based iron single-atom material (Fe-N x B / GCN12) was placed in a 5% Nafion solution diluted 10 times with water. Then, the material was evenly dispersed in the above solution by ultrasonication for 5 minutes. The above suspension was immediately applied to the surface of the glassy carbon electrode. After the material on the surface of the glassy carbon electrode was dried, electrochemical impedance spectroscopy, Taaffe curve and open circuit voltage electrochemical tests were performed in a three-electrode electrolytic cell with 0.2M Na2SO4 as the electrolyte. The test results are shown in Figure 6 shown.
[0116] from Figure 6 As can be seen in Figure (a), boron-doped carbon-based iron single-atom material (Fe-N x B / GCN12) is better than carbon-based iron single-atom materials (Fe-Nx / GCN) has a smaller arc radius, which indicates that collision doping makes the carbon-based iron single atom material have smaller resistance, thereby accelerating the electron transfer rate in the catalytic reaction. Figure 6 In the figure (b), boron-doped carbon-based iron single atom material (Fe-N x B / GCN12) is better than carbon-based iron single-atom materials (Fe-N x / GCN) has a more negative free corrosion potential, indicating that Fe-N x B / GCN12 has strong redox properties. Figure 6 In the middle (c) figure, after the open circuit voltage stabilizes, that is, when the test time is 50s, the PMS solution is added. x B / GCN12) is better than carbon-based iron single-atom materials (Fe-N x / GCN) produced a larger voltage change, indicating that boron doping enhanced the reactivity between carbon-based iron single-atom materials and PMS.
[0117] Application Example 7 Sulfamethoxazole Removal Experiment
[0118] Take 20 mg of the materials (Fe-N x / GCN,Fe-N x B / GCN4,Fe-N x B / GCN6,Fe-N x B / GCN8 and Fe-N x B / GCN12) was placed in 50mL of 5mg / L sulfamethoxazole solution. Immediately perform ultrasonic treatment for 60s. Then, add 1mM PMS reagent with a pipette and start timing. At the set time interval, 1.5mL of the reaction solution was extracted with a 5mL syringe, and then filtered through a microporous filter into a brown liquid vial containing 50.0uL Na2S2O3·5H2O (0.6M) solution to terminate the reaction, and perform the next step of analysis by liquid chromatography. The concentration change of sulfamethoxazole during the entire catalytic reaction is shown in Figure 7 .
[0119] from Figure 7 It can be seen that without the addition of catalyst, the degradation ability of pure PMS on sulfamethoxazole is very limited. x The addition of boron effectively improved the removal capacity of the reaction system for sulfamethoxazole, but the degradation efficiency per unit time gradually became slow. The incorporation of boron greatly improved the catalytic performance of the material. Boron-doped carbon-based iron single atom material (Fe-N xB / GCN12) can completely remove sulfamethoxazole in the system within 50 minutes, which fully demonstrates the advantages and practical application potential of this material in the treatment of sulfamethoxazole pollution.
[0120] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing boron-doped carbon-based iron single-atom material by two-step calcination, characterized in that: The following steps are involved: Step 1: Place the carbon-based reagent, iron reagent and soft template into anhydrous ethanol respectively; Step 2: ultrasonically treating the carbon-based reagent solution, the iron reagent solution and the soft template solution obtained in step 1, and then placing them in an oil bath and heating them to 55-70° C.; Step 3: Add the heated iron reagent solution and the soft template solution to the heated carbon-based reagent solution, wait for the ethanol to evaporate, and place in an oven to dry; Step 4: The material obtained in step 3 is simply ground and placed in a quartz boat. Argon gas is passed through the internal pipeline of the tube furnace for 10-30 minutes to exhaust all the air in the pipeline. The temperature is increased to 800-850°C at a rate of 9-10°C / min and maintained for 2-2.5 hours, then cooled to room temperature and taken out; Step 5: Grind the solid obtained in step 4, wash it with water and ethanol 3 to 4 times each, and then dry it in a vacuum drying oven for 16 to 36 hours; Step 6: Grind the dried material prepared in step 5 into powder; take 350-450 mg of the powder, then add 40-120 mg of boric acid and grind and mix thoroughly; Step 7: Place the mixture obtained in step 6 into a quartz boat, pass argon gas through the internal pipeline of the tube furnace for 10 to 30 minutes to exhaust all the air in the pipeline; increase the temperature to 400 to 450° C. at a heating rate of 9 to 10° C. / min, maintain for 2 to 2.5 hours, and then cool to room temperature before taking out; Step 8: Grind the solid obtained in step 7, wash with water and ethanol, and then dry it in a vacuum drying oven for 16 to 36 hours; Step nine: Grind the dry material prepared in step eight into powder to obtain a boron-doped carbon-based iron single atom material.
2. The method for preparing the boron-doped carbon-based iron single-atom material according to claim 1, characterized in that: The iron reagent includes ferric chloride hexahydrate; the carbon-based reagent includes chitin; the soft template includes polyether F127; and the method used is a soft template + two-step calcination strategy.
3. The method for preparing the boron-doped carbon-based iron single-atom material according to claim 1, characterized in that: In step 2, the ultrasonic time is 20-30 minutes.
4. The method for preparing the boron-doped carbon-based iron single-atom material according to claim 1, characterized in that: In step 3, the drying temperature in the oven is 50-70°C.
5. A boron-doped carbon-based iron single-atom material prepared by any method of claims 1-4.
6. The use of the boron-doped carbon-based iron single-atom material according to claim 5, characterized in that: The boron-doped carbon-based iron single-atom material is used for efficient degradation of sulfamethoxazole.
7. The use according to claim 6, characterized in that: The following steps are involved: (1) mixing sulfamethoxazole with water to obtain a sulfamethoxazole contaminated solution; (2) placing the boron-doped carbon-based iron single-atom material into the sulfamethoxazole contaminated solution obtained in step (1) and stirring; (3) Add potassium persulfate (PMS) reagent.
8. The use according to claim 7, characterized in that: The concentration of sulfamethoxazole in the sulfamethoxazole contaminated solution in step (1) is 3-5 mg / L.
9. The use according to claim 7, characterized in that: The dosage of the boron-doped carbon-based iron single-atom material in step (2) is 0.3 to 0.45 g / L.
10. The use according to claim 7, characterized in that: The dosage of the PMS reagent in step (3) is 0.6-1.2 mM.
Citation Information
Patent Citations
Monoatomic catalyst for preparation of low-carbon olefin by means of dehydrogenation of lower low-carbon hydrocarbons, and catalytic method
CN109225306A
Preparation method and application of solid acid-base catalyst for producing transformer insulating oil
CN116037164A
Iron carbide and nitrogen coordinated iron co-doped nitrogen and graphene-containing carbon material as well as preparation method and application thereof
CN117427682A